Teacher Appraisal System in one Nazarbayev Intellectual School in Kazakhstan: Teachers’ Perceptions and Experiences - Pak, Violetta (Nazarbayev University Graduate School of Education, 2020)
Teachers remain to be one of the most fundamental parts of any educational system. As such, they need an effective system to develop professionally. A Teacher Appraisal System (TAS) is one way to address this need through a systematic approach to monitoring how teachers grow. In Kazakhstan, policymakers developed TAS that aims at the systematic measurement of educators’ competences with the promotion of pedagogues based upon these competencies. Nazarbayev Intellectual Schools (NIS) in Kazakhstan provide an opportunity for piloting educational policies, practices, and reforms. In 2010, NIS created their own system for TAS. This new approach is intended to be spread to mainstream schools. By understanding the experiences and conception of NIS teachers as related to the TAS, it is then possible to know what to expect for the future implementation of TAS in mainstream schools across the country. Thus, the purpose of this study was to explore the experiences and understanding of TAS by individual teachers of TAS in one NIS school. An exploratory, qualitative case study research design was used to answer the research questions. What are the teachers’ understanding of the teacher appraisal system in one NIS school? What are the experiences of individual teachers of TAS in one NIS school? Through semi-structured interviews with six participants, the following themes were identified: motivation for professional growth, encouragement for promotional advancement, aspects to help to pass attestation, the role of appraisers, criteria of evaluation, and challenges teachers face. Findings revealed that teacher participants positively perceive the existing NIS TAS as an effective tool for professional development. Implications of this study for Kazakhstan include recommendations for school administrators, policymakers, and teachers who plan to apply for appraisal. Future studies are recommended to address the same topic from the point of mainstream schools.
Keywords: teachers’ perception, teachers’ understanding, teacher appraisal system (TAS), NIS, teacher promotion, teacher certification